KARAKTERISTIK TINDAKAN TIPPEE DALAM PRAKTIK INSIDER TRAIDING PADA PASAR MODAL INDONESIA - Putu Eva Ditayani Antari; I Gusti Agung Ayu Mas Triwulandari (Universitas Widya Gama Malang, 2019)
The practice of insider trading is a very neat offense, the object it is working on has been planned carefully and carried out gradually, so it is certainly understandable that to catch the culprit is not an easy matter. Oversight of the Financial Services Authority on the actions of insider trading actors may prevent insider trading practices by certain parties, especially the unregulated tippee (legal vacuum) in the Capital Market Law. This research is a type of normative juridical research by raising legal issues concerning the characteristics of tippee actions in the practice of insider trading on the capital market in Indonesia. The results of the study found that to be a tippee regulated in the Capital Market Law, it is necessary to have an